The hegemony of the English language and the plight of African languages : towards linguistic revolution - Ntombela, Berrington Xolani Siphosakhe (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The elevation of African languages into official status with English and Afrikaans in South Africa was meant to redress linguistic imbalances of the past. The past linguistic imbalances negatively affected mother tongue speakers of African languages. This article highlights the gravity of this imbalance from a general linguistic perspective, demonstrating how the hegemony of English continues to downplay the efforts of developing African languages for African children’s epistemic access and educational success. Among the challenges in developing African languages into the same status as English are the globalisation imperatives that are set to counter the project of decolonisation. Although there has been linguistic resistance, it has not contributed to the elevation and development of African languages. The theoretical underpinnings of the arguments in this paper are located in the critical approach. The critique is mounted not only on the hegemonic presence of the English language but on the failure of resistance to depose that hegemony and to elevate the position of African languages as viable languages of intellectual pursuit. This article therefore proposes linguistic revolution as a solution to the plight of African languages.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 8, 2024
Keywords: African languages; Linguistic decoloniality; Epistemic access; Globalisation; Social language construction; Hegemony -- South Africa; African languages; Hegemony; Globalization; Linguistic change